WEB PLOT DIGITIZER SOFTWARE: CAN IT BE USED TO MEASURE NECK POSTURE IN CLINICAL PRACTICE? - Mani, Suresh; Sharma, Shobha; Singh, Devinder Kaur Ajit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective : The aim of this study was to examine the use of WPD software to evaluate FHP using digital photogrammetry method. Method: A total of 15 adults with no history of neck pain for the past 6 months were recruited for the study. Using digital photogrammetry and sagittal head tilt, craniocervical and shoulder angles (SAs) were measured using a WPD, which is an open resource of web or Windows-based software. Result: Fifteen participants aged 17–40 years (mean 24.7±6.3 years) were examined. Sagittal head tilt and craniocervical angles were 16.35°±8.33° and 47.43°±7.97°, respectively. SA was 52.28°±12.46°. Conclusion: WPD may be used to evaluate FHP in the clinical settings. However, future research is required to determine the validity and reliability of WPD among patients with neck-related musculoskeletal disorders with a larger sample.